2011
DOI: 10.1038/ajh.2010.210
|View full text |Cite
|
Sign up to set email alerts
|

Early Inflammatory and Metabolic Changes in Association With AGTR1 Polymorphisms in Prehypertensive Subjects

Abstract: BACKGROUND The Seventh Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure in 2003 created a prehypertension category for persons with blood pressures ranging from systolic blood pressure (SBP) of 120–139 mm Hg or diastolic blood pressure (DBP) from 80 to 89 mm Hg, due to increased risk of cardiovascular disease. METHODS Our study utilized the University of California-San Diego (UCSD) Twin Hypertension Cohort. We measured comprehensive plasma cholesterol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…In particular, we stratified on the common A1166C polymorphism (rs5186) in the 39-untranslated region of the AGTR1 gene, based on its impact on mRNA stability and subsequent transcription of the AGTR1 receptor. When the CC or AC polymorphism is present, there is an increase in AGTR1 levels, which correlates with elevated blood pressures (44,48). Similarly, we found that subjects with the AC/CC allele exhibited greater vasoconstriction after DE exposure compared with the common AA allele.…”
Section: Genetic Variation and Mechanisms Of De Effectssupporting
confidence: 57%
“…In particular, we stratified on the common A1166C polymorphism (rs5186) in the 39-untranslated region of the AGTR1 gene, based on its impact on mRNA stability and subsequent transcription of the AGTR1 receptor. When the CC or AC polymorphism is present, there is an increase in AGTR1 levels, which correlates with elevated blood pressures (44,48). Similarly, we found that subjects with the AC/CC allele exhibited greater vasoconstriction after DE exposure compared with the common AA allele.…”
Section: Genetic Variation and Mechanisms Of De Effectssupporting
confidence: 57%
“…Finally, while we focused on autonomic and hemodynamic determinants of BP in this report, our prehypertensives demonstrated a BMI increment of ~2.9 kg/m 2 over their normotensive counterparts; in other reports, an early elevation of BMI in prehypertension, with its associated metabolic traits, may also be central to the syndrome (41). …”
Section: Discussionmentioning
confidence: 65%
“…Angiotensin II receptor type-1 (AGTR1) is a G-protein coupled receptor for angiotensin II, especially in the heart and kidney, and has been studied in many health conditions, including heart failure and stroke (Henskens et al, 2007;Wu et al, 2009). AGTR1 polymorphisms are associated with the susceptibility to hypertension and prehypertension in the American population (Mottl et al, 2008;Fung et al, 2011). A meta-analysis also found that the AGTR1 variant has been associated with an increased risk of hypertension in the Chinese population (Levy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%